Building with Bamboo Design and Technology of a Sustainable Architecture Second and revised edition - Minke, Gernot 1937- (Birkhäuser, 2016)
Although traditionally a building material of the warmer climate zones, bamboo is becoming increasingly popular amongst architects in the northern hemisphere; bamboo has several advantages – it is very stable, of low weight, and highly elastic, in addition to being readily available as well as renewable. The applications of bamboo in architecture have become significantly wider and diversified, so that today, even structures with large spans – such as bridges – are built with this material. The new and revised second edition of this manual provides a practical, systematic overview of the numerous potential applications and processing methods of this renewable material. The comprehensive presentation of groundbreaking bamboo buildings has been updated with more recent projects